2022
DOI: 10.3390/w14223790
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Risk Assessment of Atrazine and Diuron in Well and Surface Water of a Cornfield Rural Region

Abstract: Herbicides have contributed to increased agricultural production. However, their residual amount can cause negative effects on environmental and public health. Therefore, this work aimed to determine the occurrence of both atrazine and diuron in surface and well water and investigate their link with drinking use. The samples were collected during dry and rainy seasons in three wells and surface water from a river and a pond located in the low plains of the Ixcatepec catchment, at the Amacuáhuitl community of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Additionally, DNA-based toxicity research suggests that airborne herbicides may alter gene expression 68 , potentially leading to inherited epigenetic changes. These chemicals have been also linked to risks for the nervous system 16 . Given the potential environmental and health risks associated with residual herbicides from biomass burning, it is crucial to implement effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, DNA-based toxicity research suggests that airborne herbicides may alter gene expression 68 , potentially leading to inherited epigenetic changes. These chemicals have been also linked to risks for the nervous system 16 . Given the potential environmental and health risks associated with residual herbicides from biomass burning, it is crucial to implement effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are currently no studies available on the distribution of ATZ and DIU in agricultural residues, their presence in the environment, including soils, water, and plants have been documented. The residual amounts of ATZ and DIU in soil can undergo sorption processes or migrate into water bodies directly through runoff or indirectly through leaching and erosion processes, particularly affecting agricultural regions 16 . This mobility has been demonstrated in studies such as Vonberg et al 17 , which analyzed ATZ soil core residues from an agricultural field where ATZ had been applied before its ban in 1991, revealing an ATZ half-life value of about 2 years for the soil zone, significantly exceeding the highest ATZ half-lives found in the literature (433 days for subsurface soils).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that elevated oxidative stress, amongst other factors are implicated in the immunotoxicity effects of ATZ in mammals ( Gao et al, 2016 ). However, the relevance of this hypothesis remains to be clarified, since these concentrations of ATZ are rarely encountered in real-life human scenarios ( Lagunas-Basave et al, 2022 ; Owagboriaye et al, 2022 ; Li et al, 2023 ). The cytotoxicity of ATZ at a concentration of 15 μg/L on the erythrocytes of Lithobates spectabilis (male frog, native to Mexico) as detected by the micronucleus test, was accompanied with increases in the areas of melanin-containing melanomacrophage centers, and abnormal histological features of the liver along with a rise in the number of membrane with bumpy surfaces, apoptotic, and necrotic erythrocytes ( Méndez-Tepepa et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the year 2020 to determine the ATZ levels in 1135 lakes and reservoirs in 48 states in the US revealed that ATZ was identified in about 32% of waterbodies, at a mean concentration of 0.17 μgL −1 [ 8 ]. Reports available from Mexico and Venezuela showed that the ATZ levels were found in the range of 5.77 to 402.00 ng L −1 and 1.00–1990 ngL −1 , respectively, in the surface water [ 9 ]. It was initially thought that, since its mode of action is to prohibit photosynthesis in the desired plants, it would spare other species from its deleterious effects.…”
Section: Introductionmentioning
confidence: 99%